Potential use of Fourier transform infrared spectroscopy for differentiation of bovine and porcine gelatins - Mat Hashim, Dzulkifly; Che Man, Yaakob; Rusli, Norakasha; Mustafa, Shuhaimi; Y., Salmah; Zainul Abidin, Syahariza (Elsevier, 2010)
In order to classify unknown gelatin into their species of origin, a simple and rapid method for the qualitative determination was developed using Fourier transform infrared (FTIR) in combination with attenuated total reflectance (ATR) and discriminant analysis. The spectra were analysed using a chemometric method, principal component analysis (PCA), to classify and characterise gelatin compounds using regions of the FTIR spectra in the range of 3290–3280 cm−1 and 1660–1200 cm−1 as calibration models. Results from PCA, which were subsequently represented by the Cooman’s plot showed a clear distinction between gelatin samples of bovine and porcine origins. This qualitative approach, besides providing a rapid determination of the source of gelatin, may also be established based on a second derivative study of the FTIR spectrum to alleviate any doubt of the gelatin source for applications in the food and pharmaceutical industries.